The Analysis Study of Management of Rehabilitation in Patient with Bladder Dysfunction : A Comprehensive Systematic Review - Pretika Prameswari; Aulia Fitri (The International Journal of Medical Science and Health Research, 2024)
Background: Management of bladder dysfunction, a condition causing bladder problems, requires effective treatment strategies. PMR specialists, urologists, and gynecologists are primarily involved in this process. However, there is a lack of consensus on optimal treatment protocols, necessitating interdisciplinary collaboration and comprehensive care frameworks. Methods: This systematic review complied with the PRISMA 2020 requirements, concentrating solely on full-text papers published in English from 2014 to 2024. Editorials and review articles lacking a DOI were omitted to guarantee the use of high-quality sources. A comprehensive literature review was performed using esteemed databases such as ScienceDirect, PubMed, and SagePub to locate pertinent studies. Result: The initial database search yielded more than 3,000 publications related to the topic. Through a rigorous three-stage screening process, eight studies were identified that met the predefined inclusion criteria for detailed analysis. These selected studies underwent thorough critical evaluation, enabling an in-depth examination of the management of rehabilitation in patients with bladder dysfunction. This meticulous approach ensured that only the most relevant and high-quality studies were included in the review, providing a robust foundation for the subsequent analysis. Conclusion: Rehabilitation therapy has shown promising results in managing bladder dysfunction in neurological conditions like multiple sclerosis, stroke, and spinal cord injury. Non-invasive interventions like pelvic floor muscle training and electrostimulation improve urinary function and quality of life. Advanced therapeutic approaches like high-intensity-focused electromagnetic therapy and virtual reality offer personalized treatment options.